Elevated levels of nitrous dioxide are associated with lower AMH levels: a real-world analysis. Issue 11 (20th September 2020) - La Marca, Antonio; Spaggiari, Giorgia; Domenici, Daniela; Grassi, Roberto; Casonati, Andrea; Baraldi, Enrica; Trenti, Tommaso; Simoni, Manuela; Santi, Daniele
Abstract: STUDY QUESTION: Are there any associations between environmental pollutants and ovarian reserve, expressed by anti-Mullerian hormone (AMH) serum levels? SUMMARY ANSWER: In this first real-world approach to demonstrate the relationship between air pollutants and serum AMH levels, adverse associations were observed for nitrogen dioxide (NO2 ) but not with particulate matter. WHAT IS KNOWN ALREADY: In recent years, air pollution has emerged as a potential disrupter to the homeostasis of physiological hormones, possibly affecting human reproduction. Although the influence of age and smoking on AMH levels is largely accepted, the relationship between AMH and the environment has not currently been established. STUDY DESIGN, SIZE, DURATION: A longitudinal, observational, retrospective, real-world study was carried out, including all AMH measurements performed in a single laboratory from January 2007 to October 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Serum AMH data were connected to patients' age and residential address, to include air pollution data after geo-localisation. The air pollution considered daily particulate matter (PM) and NO2 values. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 1463 AMH measurements were collected (mean 1.94 ng/ml, median 0.90 ng/ml). AMH was inversely related to patients' age in women older than 25 years (adjusted R -squared 0.120, P  < 0.001), but not in those younger than 25 years (adjusted R -squared 0.068, P  = 0.055). AMH levels were inversely related to environmental pollutants, such as PM10 (Rho = −0.088, P  = 0.001), PM2.5 (Rho = −0.062, P  = 0.021) and NO2 (Rho = −0.111, P  < 0.001). After subdividing the dataset into quartiles for PM10 and PM2.5, the influence of age on AMH serum levels was found to be a stronger influence than that exerted by PM ( P  = 0.833 and P  = 0.370, respectively). On the contrary, considering NO2 quartiles, higher AMH levels were observed in third quartile compared to fourth quartile, even after adjustment for age ( P  = 0.028), indicating a stronger influence of NO2 exposure on AMH serum levels. Considering an AMH cut-off of 0.3 ng/ml, a significant higher frequency of women with severe ovarian reserve reduction in the fourth quartile was shown only for NO2 ( P  = 0.010). LIMITATIONS, REASONS FOR CAUTION: Several limitations should be underlined, such as the lack of information about work and life habits of each patient and the retrospective nature of the analysis performed on real-world data. WIDER IMPLICATIONS OF THE FINDINGS: Although the genetic component is highly predictive for defining the ovarian reserve at birth, potentially modifiable environmental factors could influence the rate of decline in AMH and ovarian reserve during adulthood. STUDY FUNDINGCOMPETING INTEREST(S): Authors have neither funding nor competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.